English for pre-diploma MOOC / Iza Faradiba Mohammad Pate, Nora Harun and Nurul Ain Hasni - Mohammad Pate, Iza Faradiba; Harun, Nora; Hasni, Nurul Ain (Universiti Teknologi MARA, 2018)
Over the years, there are numerous effective learning strategies suggested in the area of language learning which are having a clear motivation (Gardner and Lambert,1972; Krashen, 1982), low affective filter (Dulay and Burt, 1977; Krashen, 1988) and continuous language practice or drills (Gass and Selinker, 2008). On the contrary, conventional language lessons fail to address the gap in increasing learners’ motivation, overcoming anxiety during peer-to-peer interactions and discussion, which result in frustrations among the learners. In addition, an exorbitant number of students in a class makes it impossible for the instructor to focus on individual learners. English for Pre-Diploma MOOC helps to create fun and engaging learning experience for learners to increase their motivation in learning the language. It also facilitates the learners especially the introverts to discover and explore the language in a more interactive and less threatening setting. Furthermore, it attempts to promote critical thinking skills and knowledge of the world through the activities and online discussions. The extended activities in the MOOC elicit high order responses from the learners while the teaching module consists of appealing themes and interactive teaching videos that cater to the interest and unique individual learning styles. Some of the noticeable impacts on learners are they become more active and responsive as learning happens at any time, at their own pace and convenience. Moreover, they benefit from interactions with learners of various backgrounds and maturity levels. As a result, they become highly motivated, independent, critical and reliable learners of the language